Detrital zircon provenance of Triassic sandstone of the Algarve Basin (SW Iberia): Evidence of Gondwana and Laurussian type sources of sediment - Gama, Cristina (2022)
Detrital zircon populations from six samples of upper Triassic sandstone (Algarve Basin) were analysed, yielding mostly Precambrian ages. zircon age populations of the Triassic sandstone sampled from the western and central sectors of the basin are distinct, suggesting local recycling and/or lateral changes in their sources. Our findings and the available detrital zircon ages from the Palaeozoic terranes of SW Iberia, Nova Scotia and NW Morocco were jointly examined using the Kolmogorov–Smirnov test and multidimensional scaling diagrams. The obtained results enable direct discrimination of competing Laurussian-type and Gondwanan-type sediment sources, involving recycling and mixing relationships. The detrital zircon populations of the Algarve Triassic sandstone are very different from those of the lower–upper Carboniferous Mértola and Mira formations (South Portuguese Zone), upper Devonian – lower Carboniferous Horta da Torre, Represa and Santa Iria formations (Pulo do Lobo Zone), and the late Carboniferous Santa Susana and early Permian Viar basins, which are ruled out as potential sources. The detrital zircon populations of Triassic sandstone from the central sector and those from the Ossa–Morena Zone Ediacaran–Cambrian siliciclastic rocks, upper Devonian –Carboniferous Ronquillo, Tercenas, Phyllite-Quartzite and Brejeira formations (South Portuguese Zone), and Frasnian siliciclastic rocks of the Pulo do Lobo Zone are not statistically distinguishable. Thus, sedimentation in the central sector was influenced by Gondwanan- and Laurussian-type putative sources exposed in SW Iberia, in contrast to the western sector, where Meguma Terrane and Sehoul Block Cambrian siliciclastic rocks allegedly constituted the main (Laurussian-type) sources. These findings provide insights into the denudation of distinctive source terranes distributed along the late Palaeozoic suture zone that juxtaposed the Laurussian and Gondwanan margins.